Communicating PNPLA3 genetic risk status for NAFLD among Mexican-origin men - Villavicencio, Edgar A.; Maldonado, Adriana; Crocker, Rebecca M.; Guan, Yue; Stallman, Chris; Garcia, David O. (Frontiers in Public Health, 2023)
The burden of non-alcoholic fatty liver disease (NAFLD) continues to disproportionately impact under-resourced communities in the U.S., particularly Mexican-origin populations. Genetic polymorphisms such as the rs738409 C/G variant in patatin-like phospholipase domain-containing 3 (PNPLA3) have been associated with higher prevalence of and progression along the NAFLD spectrum. This qualitative study conducted in the U.S. Southwest aimed to assess Mexican-origin men’s experience receiving genetic testing for PNPLA3 risk carrier status. The interview guide included questions exploring participants’ insights on how genetic risk status was delivered, how the information influenced their motivation for lifestyle modification to reduce NAFLD risk, and any knowledge sharing that occurred with family members after learning of their PNPLA3 risk status. Semi-structured interviews were conducted with 17 Mexican-origin men whose NAFLD status and genetic predisposition were determined as part of a previous cross-sectional study. Interviews were conducted and audio recorded in English (n=6) and Spanish (n=11) and uploaded into NVivo software for data analysis and interpretation. Guided by the Health Belief Model, a thematic analysis approach was used to identify primary themes. Results highlighted men’s preference for receiving this type of genetic risk information through a letter sent to their homes. General comprehension of PNPLA3 risk status was deemed high and most men stated sharing their genetic predisposition to NAFLD with their immediate family members. Participants also indicated that family and awareness of this genetic risk acted as primary motivators for implementing behavior changes (e.g., diet, physical activity) toward the prevention of more severe liver conditions. Findings from this qualitative study suggest the feasibility of communicating genetic risk for NAFLD among Mexican-origin men. Future strategies for the dissemination of genetic risk results among Mexican-origin individuals should consider familial and cultural appropriate strategies.